Microbial Communities in Soils and Endosphere of Solanum tuberosum L. and their Response to Long-Term Fertilization - Kracmarova, Martina; Karpiskova, Jana; Uhlik, Ondrej; Strejcek, Michal; Szakova, Jirina; Balik, Jiri; Demnerova, Katerina; Stiborova, Hana (Microorganisms, 2020)
An understanding of how fertilization influences endophytes is crucial for sustainable agriculture, since the manipulation of the plant microbiome could affect plant fitness and productivity. This study was focused on the response of microbial communities in the soil and tubers to the regular application of manure (MF; 330 kg N/ha), sewage sludge (SF; 330 and SF3x; 990 kg N/ha), and chemical fertilizer (NPK; 330-90-300 kg N-P-K/ha). Unfertilized soil was used as a control (CF), and the experiment was set up at two distinct sites. All fertilization treatments significantly altered the prokaryotic and fungal communities in soil, whereas the influence of fertilization on the community of endophytes differed for each site. At the site with cambisol, prokaryotic and fungal endophytes were significantly shifted by MF and SF3 treatments. At the site with chernozem, neither the prokaryotic nor fungal endophytic communities were significantly associated with fertilization treatments. Fertilization significantly increased the relative abundance of the plant-beneficial bacteria Stenotrophomonas, Sphingomonas and the arbuscular mycorrhizal fungi. In tubers, the relative abundance of Fusarium was lower in MF-treated soil compared to CF. Although fertilization treatments clearly influenced the soil and endophytic community structure, we did not find any indication of human pathogens being transmitted into tubers via organic fertilizers.
Keywords: NPK; sewage sludge; soil microbial communities; endophytic communities; manure